1st Epistle to the Corinthians of Apostle Paul in the Modern Biblical Studies - Ivanova, Emanuela (Forum Theologicum Sardicense, 2025)
Emanuela Ivanova, 1st Epistle to the Corinthians of Apostle Paul in the Modern Biblical Studies. The author focuses on the First Epistle to the Corinthians, examining aspects such as its authorship, date and place of writing, canonicity, and its position among the New Testament books. The study also considers the addressee community within its cultural and historical context, as well as its language, style, structure, content, and intertextuality within the New Testament canon. Contemporary research on this subject can be categorized into two main groups: studies that address the epistle as a whole or specific themes within it, and commentaries. These studies are further divided by confession into Orthodox, Catholic, and Protestant perspectives.